Propuesta de un plan estratégico para la comercializadora de vehículos Maldonado Covehmal de la ciudad de Loja periodo 2013-2018 - Martínez Jiménez, José Danilo (2014)
This research project was focused to make a "Strategic PLAN for the marketer of vehicles MALDONADO COVEHMAL from the city of LOJA period 2013 - 2018", because nowadays need to be leaders in: market and increase your profitability versus the competition. With the purpose of obtaining information about the current situation of Covehmal it has had to carry out a field study using a methodology according to the needs of this project, methods include the inductive, analytic, deductive, descriptive; as research techniques: survey and interview, the first carried out to employees and customers; and the interview focused on his Manager. Tabulated results of surveys and interview continued by analyzing the external and the internal. Within the outer discussed macroeconomic factors such as the economic, technological, political, legal, social, environmental and the five forces Porter. Each of these determine the opportunities and threats of Covehmal, concluding with the development of the matrix of evaluation of external factors (EFE) with a total of 2.38 which means that Covehmal has good opportunities (1.46) threats which are more (0.92), however it can take advantage of opportunities offered by a market. Continued by analyzing the internal environment of Covehmal based on the responses of customers, employees and Manager of this business, determined the strengths and weaknesses, preparing the matrix of evaluation of internal factors (EFI), with a total weighted 2.46, establishing a high degree of (1.43) strengths against weaknesses (0.89). Then was the SWOT matrix, the strengths are: proper location of the company, good service to the client, sufficient vehicles, years of experience, rates loans accessible to customers, economic strength and guaranteed quality products. Opportunities are focused: increase in trade in vehicles, restriction to import new vehicles, accessibility to the technology on the market, used vehicles of brands and entering new markets or segments. Threats found in the marketing of vehicles Covehmal were: decrease in remittances from migrants, wage political Inadecuada, high bank interest rates, high taxes for spare parts for used vehicles, poverty generates unemployment, growth of competition and appearance of substitute products. And weaknesses are: high prices compared to competition, insufficient publicity and promotion of Covehmal, lack of training for staff, lack of a manual functions, manual of recruitment of staff, lack of structure, lack of a branch and the absence of a corporate philosophy (mission, vision and values), organic. Taking basic SWOT matrix, ran the matrix of high impact and combination of analysis FO, DO, FA, DA to the approach of the strategic objectives that were six: a) establish strategic alliances between the marketer and the financial institutions to get credit in the purchase of used vehicles, b) define a publicity and promotion plan to strengthen the image and increase sales of vehicles((c) define new sales policy to increase the share in the market, d) design a training plan for staff of Covehmal for having a contingent human resource; (e) define an organizational structure and administrative manuals for the comercializadora Covehmal; and (f) create a branch of the marketer of vehicles Covehmal to neutralize competition. Continued to make the proposal for the fulfilment of the objectives of Covehmal begun by defining the corporate philosophy (mission, vision and values), a publicity and promotion plan, a training plan, the preparation of organization charts together with a manual functions and a manual on recruitment and selection of personnel, sales policy approach; the opening of a telephone line to improve customer service; and the contract with several financial institutions that serve as intermediaries for the granting of loans to customers wishing to purchase a vehicle in Covehmal, the creation of a branch for this marketer. The budget for these activities amounts to $228.199, 82. The complementary part of the present work, presents the conclusions and recommendations which are final propositions made strategic planning.